Neurogenesis and Viral Infection - Ihunwo, Amadi Ogonda; Perego, Jessica; Martino, Gianvito; Vicenzi, Elisa; Panina-Bordignon, Paola (Frontiers in Immunology, 2022)
Neural stem cells (NSCs) are multipotent stem cells present in the fetal and adult mammalian brain, which can self-renew and give rise to neurons and supporting cells. The self-renewal and differentiation capacity are tightly regulated by complex interactions between intrinsic and extrinsic signals provided by neighboring cells in the niche and by distant sources. Ample evidence supports the important role of NSCs in plasticity, aging, disease, and repair of the nervous system. Indeed, activation of NSCs or their transplantation into injured areas of the central nervous system can lead to regeneration in animal models. Viral invasion of NSCs can negatively affect neurogenesis and synaptogenesis, with consequent cell death, impairment of cell cycle progression, premature differentiation and defective cell division, leading to depletion of neural progenitors of the cortical layer. Herein, we will review the current understanding of Zika virus (ZIKV) infection of the fetal brain and the NSCs that are the preferential population targeted by ZIKV. Furthermore, the potential neurotropic properties of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which may cause direct neurological damage, will be discussed.